2013
DOI: 10.1080/17518253.2012.738371
|View full text |Cite
|
Sign up to set email alerts
|

A simple and eco-sustainable method for theO-Boc protection/deprotection of various phenolic structures under water-mediated/catalyst-free conditions

Abstract: A greener, efficient, and chemoselective protocol for O-Boc protection/deprotection of a wide range of phenol derivatives is reported under catalyst-free conditions in water-related systems. Unlike previous reports, no additional reagents or catalysts were used, and workup fulfils green chemistry requirements, making the present method even more interesting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…The final step in the preparation of the copolymer precursor was the deprotection of the hydrazide functional groups (LC-NHNH 2 ) using a simple and effective procedure under mild conditions [ 32 ]. During this reaction, complete deprotection occurred as proved by NMR.…”
Section: Resultsmentioning
confidence: 99%
“…The final step in the preparation of the copolymer precursor was the deprotection of the hydrazide functional groups (LC-NHNH 2 ) using a simple and effective procedure under mild conditions [ 32 ]. During this reaction, complete deprotection occurred as proved by NMR.…”
Section: Resultsmentioning
confidence: 99%
“…In general, this tunable Boc modification process was designed via a system thinking, including availability of raw lignin, economical/green modification, potentiality of drop-in-change to current thermoplastic processing, modification impact on microbial degradability/disposed environment at the end of use life; hence the holistic consideration makes this alternative method for upgrade of technical lignins very practical for future industrial application. Di-tert-butyl dicarbonate (Boc2O) is well known as a reagent for protection of amines and alcohols in organic synthesis in the presence of base catalyst [21][22][23]. In addition, it is also used as a dehydrating agent in reaction with carboxylic acids [24].…”
Section: Common Lignin Modification Strategiesmentioning
confidence: 99%
“…Di-tert-butyl dicarbonate (Boc2O) is well known as a reagent for protection of amines and alcohols in organic synthesis in the presence of base catalyst. [21][22][23] In addition, it is also used as a dehydrating agent in reaction with carboxylic acids. 24 A recent revisited reaction of alcohols with Boc2O in the presence of 4-dimethylaminopyridine (DMAP) indicated that the pKa of the alcohols strongly affect formation of products (symmetrical carbonates or O-Boc) and the reaction rate;…”
Section: Scheme 2 Structure Of Lignin and A Postulated Modified Strumentioning
confidence: 99%